Impact of bictegravir/emtricitabine/tenofovir alafenamide on health-related quality of life and economic outcomes in HIV care: Substudy of the BIC-NOW clinical trial - Sergio Sequera-Arquelladas; María J. Vivancos; David Vinuesa; Antonio Collado; Ignacio De Los Santos; Patricia Sorni; Noemi Cabello-Clotet; Marta Montero; Carlos Ramos Font; Alberto Terron; Maria José Galindo; Onofre Martinez; et al. (PLoS ONE, 2025)
Background The BICNOW clinical trial evaluated the effectiveness, safety, satisfaction, adherence to treatment, and retention in the system of a rapid initiation strategy with bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF) in naïve HIV-infected individuals. It also assessed the burden of this infection on individuals and healthcare systems using various instruments, participant questionnaires, and pharmacoeconomic evaluations of this antiretroviral therapy (ART). This substudy focused on changes in the health-related quality of life (HRQoL) of participants and on the economic impact of this rapid initiation strategy. Methods and Findings Patients were recruited for this phase IV, multicenter, open, single-branch clinical trial with 48-week follow-up between November 2020 and July 2022. HRQoL data were gathered using EQ-5D-3L and dichotomized HIV-SI questionnaires. In the cost-utility pharmacoeconomic analysis, data in the literature were used for comparators. The 208 participants had a mean age of 34 (27–44) years, 87·5% were male, 42·9% had completed higher education, and 67·1% were employed. The mean EQ-5D questionnaire score was significantly increased at 48 weeks versus baseline (0·940 ± 0·117 vs. 0·959 ± 0·083, p = 0·012), and the utility value in quality-adjusted life years (QALYs) was 0·877 ± 0·093. There was a significant improvement in the “usual activities” dimension (10·8 vs 4·1% p = 0·036). The Moses extreme reaction test showed a significant difference in all dimensions between participants in AIDS versus non-AIDS stage (p < 0·001). HIV-SI results revealed a significantly smaller percentage of participants with bothersome symptoms at 48 weeks (75·4 vs. 62·2%, p = 0·035). The pharmacoeconomic study indicated a value of €6,550·21/QALY gained with this ART. Conclusions BIC/FTC/TAF is an appropriate rapid initiation strategy in naïve PLHIV that improves their quality of life. It is pharmacoeconomically feasible and offers superior long-term health outcomes in comparison to other approaches. (NCT06177574).